Diseño de una ruta agroturística para el cantón El Pangui, provincia de Zamora Chinchipe - Camacho Aillón, Janela Cristina (2023)
The general objective of this work is to propose an agrotourism route as a contribution to the development of tourism in the canton of El Pangui, Zamora Chinchipe province. For the development of the research work it was necessary to propose the following specific objectives: To make a diagnosis of the agricultural farms that have the potential for the development of agrotourism in El Pangui canton; to do this, it was used cards that allowed to evaluate the potential of the agricultural and livestock farms, as well as to identify the different agricultural, livestock and handicraft products they have, after that a matrix of stakeholders was created, finally, a cross SWOT was carried out. . The second objective was to design the agrotourism route for El Pangui canton, Zamora Chinchipe province; it was designed through 3 phases. The first allowed to establish the structure of the route; the second to determine the services to be included in the route; and the third to establish the costs and usefulness of the route. The third objective was to formulate strategies to promote the agrotourism route in the canton of El Pangui, province of Zamora Chinchipe, using a matrix that established the activities, objectives, tools, and people who are responsible for each of the strategies. The results show that the farms have agro-tourism potential, their owners are willing to collaborate in the development of agro-tourism activities, there is the presence of tourist attractions related to the farms and they are in a good condition that can be exploited. After that, the agro-tourism route was designed with a duration of 2 days and 1 night, and based on these promotional strategies were proposed for the physical route (OPI, advertising in urban buses) and digital (tourist brand, website, and social networks). Finally, it is concluded that the agricultural farms of the canton have great potential for the development of agrotourism, the designed tourism product will generate economic development within the farms, and will also be a main axis in the reactivation of tourism in the canton.